Humans in the Perspective of the Qur'an and Its Implications for the Development of Student Character in Elementary Education - Alam Jaya; Nurlidiawati Nurlidiawati; Afifuddin Harisah (Yayasan Zia Salsabila, 2026)
This study discusses the concept of human beings in the perspective of the Qur’an and its relevance to character education development in basic education. This research employed a descriptive qualitative method using a library research approach. The findings reveal that humans are monodualistic beings possessing intellect, nafs, qalb, ruh, and fitrah which must be developed in balance through Islamic education. Qur’an-based character education plays an important role in shaping students who are moral, responsible, and spiritually, intellectually, emotionally, and socially balanced. Character development is carried out through teaching, role modeling, habituation, and collaboration between teachers and parents in addressing the challenges of the digital era.